Strategi Manajemen Pengembangan Peserta Didik di SMA Plus Assalam - Badrudin, Badrudin; Muzakki, Ahsyaf; Hodijah, Anisa Siti (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Students are the main and most important element in education, without students there will be no possible learning process in the classroom. The research was conducted at SMA Plus Assalaam. This study aims to see the development of student management at SMA Plus Assalaam. Researchers in researching SMA Plus Assalaam used field research. This research uses a qualitative approach with a qualitative descriptive orientation. Data collection techniques that are in accordance with the focus and objectives of the study, then carried out using three techniques, namely observation, interview (interview) and documentation. The management of student development used by researchers is the mechanism for accepting students, the selection process and orientation activities for new students, coaching students at SMA Plus Assalaam.